Megarthrus of China. Part 2. Megarthrus basicornis Fauvel, 1904 with description of a new species from Mount Emei (Coleoptera: Staphylinidae: Proteininae) - Liu, Zhiping; Cuccodoro, Giulio (Zootaxa, 2020)
Megarthrus budai Liu and Cuccodoro sp. nov. from Sichuan province in China is described. It is the first record of the genus from Mount Emei, a temperate biodiversity-rich mountain to which this new species seems to be endemic. Megarthrus basicornis Fauvel, 1904, known so far only from India and Nepal, is reported from China for the first time.These two species have many features found mainly in members of the predominantly Holarctic and African M. depressus supergroup of species.